Comparative evaluation of different composite wall materials for encapsulation of Justicia carnea (Brazilian plume) leaves extract - Oluwatoyin Ajoke Oladeji; Olugbenga Olufemi Awolu (Exploration of Foods and Foodomics)
Aim: The study evaluated the influence of different wall materials on the bioactive compounds in encapsulated Justicia carnea leaves extract. Methods: Combinations of gelatin with maltodextrin or starch, and gum arabic with maltodextrin or starch were prepared in ratios of 1:3 to create four types of wall matrices. Each combination was dissolved in water to obtain 20% w/v solutions. J. carnea leaves were extracted, concentrated, and the resulting extract added to the wall material at a ratio of 1:2 and homogenized. Encapsulation was achieved through homogenization at 12,000 rpm for 30 min, followed by freeze drying. The resulting microcapsules were characterized using a scanning electron microscope (SEM) and differential scanning calorimeter (DSC). Physicochemical properties, pigment concentrations, and micronutrient compositions of the microcapsules were also evaluated using standard methods. Results: Carotenoids, chlorophyll, and anthocyanin were significantly higher (P ≤ 0.05) in the sample containing starch and gelatin [gelatin + starch + core (DGES)] as the wall matrix compared to other samples. Vitamins E and D, calcium (Ca), and manganese (Mn) in sample gum arabic + starch + core (CGS; blend of gum arabic starch) and sample DGES were not significantly different from each other. DGES exhibited significantly lower (60.19%) solubility than others (60.48–70.86%) and the highest (76.72%) encapsulation efficiency. SEM analysis revealed smooth surfaces and mostly polyhedral shapes, with particle sizes ranging from 10.534–14.159 μm across all samples. DSC analysis revealed that the particles are endothermic and amorphous in nature, except for the CGS sample, which became semi-crystalline at about 203.2°C. Conclusions: The study showed that a composite wall material comprising starch and gelatin demonstrates enhanced effectiveness in the encapsulation of J. carnea leaves bioactive compounds.